ANTHROPOMETRIC CHARACTERISTICS AND PHYSICAL FITNESS OF URBAN AND RURAL 8-10 YEARS OLD SCHOOL GIRLS OF BAHAWALPUR, PAKISTAN (International Journal of Physiotherapy, 2019)
Background: The assessment of anthropometric characteristics and physical fitness assist the researcher in comparing the growth and health status of urban and rural school girls. Purpose of this research was to examine anthropometric characteristics and physical fitness of urban and rural school girls of district Bahawalpur, Pakistan.Methods: The participants were government primary schoolgirls (urban = 200), and (rural = 200), within the age of 8-10 years. The selected anthropometric and physical fitness variables were stature, body mass, skinfolds, girths, breadths, lengths, speed, standing broad jump, agility, ball throw, handgrip strength, endurance, and flexibility. A student t-test was applied to assess the difference between urban and rural school girls in their anthropometric and physical fitness measures.Results: Results showed the urban school girl was significantly superior in body mass, iliac-crest skinfold(P< .04), abdominal skinfold(P< .04), waist girth (P< .04), hip girth (P< .01), thigh girth(P< .01), arm length, and hand length. In contrast, the rural school girls were significantly higher in speed(P< .02), agility(P< .02), ball throw (P< .02), flexibility( P< .03), run and walk (P< .04) than the urban school girls.Conclusion: It is concluded the urban school girls were higher in skin folds and girths, indicate high body fats than rural school girls. As a result, urban school girls were lower in fitness capacity than rural because higher body fat reduces fitness performance. It is suggested the parents and school administration focus to provide such activities to improve physical fitness and reduce body fats of urban school girls. The future study focusses on investigating the effects of food intake on the anthropometric characteristics, and physical fitness of urban and rural school children.